Pengaruh Media Sosial Dalam Strategi Pemasaran Produk Pada Usaha Mikro Kecil dan Menengah (UMKM) - Sifa Uchtiat Suhita; Fikri Amalia Rosyada; Marcellina Rifani (UIN K.H. Abdurrahman Wahid Pekalongan, 2022)
Social media is now closely related to people's lives. In Indonesia, more than half of the population uses social media in their daily life. Marketing using social media is most widely used by entrepreneurs, because it is easier to use and can be directly reached by consumers. For this reason, entrepreneurs are required to be able to create creative ideas and new innovations that can attract consumers. In writing this scientific paper, the research method used is descriptive qualitative research. The research subjects in this study were Micro, Small and Medium Enterprises (MSME) who provided research data through interviews with purposive sampling technique. Based on the results of qualitative research using interview and observation techniques as well as the data that the authors have collected, it can be concluded that social media marketing has a very large influence on product marketing because it can increase sales volume and also increase profits for Micro, Small and Medium Enterprises (MSME).